Efficacy and safety of antifibrotic drugs for interstitial lung diseases other than IPF: A systematic review, meta-analysis and trial sequential analysis - Mei Yang; Yuying Tan; Ting Yang; Dan Xu; Mei Chen; Lei Chen (PLoS ONE, 2025)
Background The therapeutic role of antifibrotic therapy has been well-established in idiopathic pulmonary fibrosis (IPF). However, its efficacy and safety for interstitial lung diseases (ILDs) other than IPF are not fully understood. Methods We updated a systematic review with meta-analysis and trial sequential analysis (TSA) of randomized controlled trials and prospective studies on antifibrotic drug (nintedanib or pirfenidone) vs other intervention (placebo, no intervention or conventional treatment) in non-IPF ILDs. The primary outcomes were absolute change in forced vital capacity (FVC), all-cause mortality and serious adverse events (SAEs). The risk of bias was rated with the RoB2 tool and certainty of evidence was assessed by the GRADE approach. Results 17 studies with 1908 patients were included. For the primary outcomes, pooled analyses of four trials with low risk of bias showed that antifibrotic drugs significantly ameliorated FVC decline (mean difference 86.21; 95% CI 49.38 to 123.03; I2 = 64%; TSA-adjusted CI 40.86 to 131.56). Based on five trials with low risk of bias, no difference was observed in all-cause mortality (RR 0.87; 95% CI 0.53 to 1.43; I2 = 0%; TSA-adjusted CI 0.12 to 6.53) and SAEs (RR 0.97; 95% CI 0.83 to 1.13; I2 = 0%; TSA-adjusted CI 0.74 to 1.28) between groups. However, based on two studies with 324 patients, benefit of antifibrotic drugs in FVC was not shown in the subgroup taking mycophenolate (mean difference 17.08; 95% CI -56.22 to 90.37), which also had higher risk of SAEs (RR 1.71; 95% CI 1.09 to 2.70), although both were contested by TSA. Conclusion Our study suggests that antifibrotic drugs are beneficial for patients with non-IPF ILDs in slowing disease progression, whereas may not correlate to all-cause mortality and SAEs. However, for patients taking mycophenolate, antifibrotic drugs may do more harm than good. More investigations are warranted to validate current findings.